The effect of age ,gender, type of feeding and receiving atreatment on the distribution of Enterovirus infection among chidren in Al- Diwaniyah city ,lraq - Al-fatlawi, Mohammed Sarim; Ghaidaa J. Mohammed (Al-Qadisiyah Journal of Pure Science, 2020)
In developed and developing countries, gastrointestinal infections still account for significant morbidity and mortality rates. The most common type of gastrointestinal infection is ’diarrhea’ (rapid production of more or less fluid-like repeated intestinal evacuations). Rotavirus, Astrovirus and enteric Adenovirus is the most common cause of severe diarrhea in children under 5 years old of age. So, this study aimed to detect these viruses in children under five years old who suffered from acute gastrointestinal infections in Al-Diwaniyah city . The Study has been done on 90 fecal samples collected from children with acute gastroenteritis from children < 5 years old. All stool specimens were examined by a real-time polymerase chain reaction ( RT-PCR) for rotavirus, astrovirus and adenovirus-positive specimens by using different primers of a specific type. The results showed the presence of viruses genes in 53 samples (58.88) out of a totally 90 samples. Among these positive results, 16.66% was for Rotavirus, Astrovirus (7.77% ) and Adenovirus (5.55%) , there was also a mixed infection between (Rotavirus & Astrovirus) in the rate of (12.22%), (Rotavirus & Adenovirus) , in the rate of (5.55%) and 6.66 (adenovirus & astrovirus) . The rate of Enterovirusrs was high in the first year of life followed by less than three years of age, the ratios were 60.65% and 75% respectively. Moreover, the infections were observed at 57.14% in males and 61.76% in females. Also, the viruses detected in (59.32%)and (58.06%)samples from children with mixed feeding and breastfeeding, respectively. In addition, the infection rates in children who took treatment and those who did not before diagnosing the type of infection were (53.96%)and (70.37%) sample respectively, as there were no significant differences in the type of feeding and treatment,(p value< 0.05). Regarding the high frequency of infections with rotavirus, astrovirus and adenovirus, continuous monitoring is required to inform, diarrhea prevention programmes, as well as information on new enteroviruses strains. This will help policy-makers make decisions about the introduction of rotavirus, astrovirus and adenovirus vaccines.